Animal snuggles : affection in the animal kingdom - Reid, Aimee (Sourcebooks eXplore, 2024)
"This heartwarming, lullaby-like nonfiction picture book combines animal facts with a comforting message of love and belonging. With back matter about ways animals show love included, this sweet book is perfect for homes, schools, and libraries!"--